"Fatigue-Crack Propagation Behavior in Microcapsule-Containing Self-Healing Polymeric Networks". (November 2022) - Fugolin, Ana P.P.; Ferracane, Jack L.; Pfeifer, Carmem S.
Graphical abstract: Highlights: A high-toughness healing agent system containing N, N -Dimethylacrylamide (DMAM) was specifically designed for microcapsule-based self-healing dental polymers. DMAM works as a cushioning agent. Microcapsules increase the overall fracture toughness of the material. Significant higher energy is required to crack propagation in microcapsule-containing polymers. Abstract: Over the last years, research on the design of dental self-healing polymers has grown dramatically. It is related to the promising potential of maximizing the clinical lifespan of dental restorations that this strategy holds. In this manuscript, the microcapsule-based strategy is innovated by incorporating the high toughness component N, N -Dimethylacrylamide (DMAM) into the healing agent systems and analyzing in-depth the change in crack propagation behavior induced by the addition of microcapsules into the highly crosslinked polymeric network. In general, the addition of the hydrophilic and high vapor pressure DMAM into the healing agent systems imposed a challenge for the microencapsulation, which highlighted the importance of tailoring the properties of the capsules' shells according to the core composition. The addition of DMAM as cushioning agent proved to be a successful strategy since it resulted in increased G'/G" crossover time from 0.06 (control) to 0.57 s and decreased storage modulus from 8.0 (control) to 0.5GPa. In addition, the incorporation of microcapsules within the polymerized networks provided obstacles to crack propagation, which translated to an overall reinforcement of the polymeric network, as evidenced by the increase in toughness up to 50 % and energy required to propagate cracks up to 100 % in systems containing DMAM at 20 wt%.